Indonesian crisis communication response after deliberate forest fires and transboundary haze - Mohammed Fadel Arandas,; Loh, Yoke Ling (Penerbit Universiti Kebangsaan Malaysia, 2020)
The issue of deliberate forest fires that set illegally in Indonesia by plantation companies in their slashand-burn forests to clear lands for lucrative palm oil plantations and its caused transboundary haze became a hot issue for discussion. These fires have a negative influence on Indonesia and its neighbourhood countries, especially on their financial and human resources such as environment, economy, properties, and people. Using the right strategies in responding to any crisis determines the success of its management and coping with that crisis with minimal losses. This study aimed to examine the communication crisis response by Indonesia to this crisis by using image repair theory. Also, this study examined how image repair strategies were used by Indonesia. This study analysed the content of news stories from the website of the New Straits Times newspaper. The time frame of this study was from 2015 to 2019. A total of 87 news stories have pertained to Indonesian response, and 37 stories included image repair strategies. Among the strategies of image repair theory, corrective action strategy was the most dominant with 70%, followed by 10.8% for each shift the blame and attack accuser. The least used strategies were mortification and simple denial with 5.4% and 2.7% respectively.